PENGARUH HARGA DAN SALURAN DISTRIBUSI TERHADAP VOLUME PENJUALAN PADA PT. BANTEN MUDA MANDIRI CIKEUSAL SERANG - Suhandi, Suhandi (Jurnal Valuasi: Jurnal Ilmiah Ilmu Manajemen dan Kewirausahaan, 2024)
PT.Banten Muda Mandiri is a company that produces and sells building materials in the form of concrete for fences, roads, bridges and so on, which is located at Jalan.Raya Cikeusal Panosogan Kampung.Dukuh RT.13/RW.03, Cikeusal Village, Serang Regency. The aim of this research is to determine the effect of price and distribution channels on sales volume at PT Banten Muda Mandiri Cikeusal Serang. In this research the method used is a quantitative method with an associative approach. This research has a population of 100 by taking a sample of 80 respondents. Data management techniques were analyzed using the classical assumption test, normality test, multicollinearity test, heteroscedasticity test, multiple linear regression analysis, coefficient of determination, hypothesis testing, namely the t test and f test. Based on the research results, the effect of price on sales volume was obtained through the t test of (0.739 > 0.05) and the calculated t value was (0.335 < t table value 1.99085) and the effect of distribution channels on sales volume was obtained through the t test of ( 0.000 < 0.05) and the calculated t value (7.190 > t table value 1.99085). In the simultaneous test (0.000 < 0.05) and calculated F (43.579 > F table value 3.12). So it can be concluded that price and distribution channels partially and simultaneously have a positive and significant effect on sales volume at PT. Banten Muda Mandiri Cikeusal attack